Developing Personal Selling SOP, Improving Website and Improving Company Profile of MSME of PT. Selula Dwiphaloka Teknologi - Fabian Danandjaya Puspadewa; Hasnul Suhaimi (Institut Teknologi Sepuluh Nopember, 2019)
The increasing number of MSMEs (Micro, Small and Medium Enterprises) in Indonesia has had a positive contribution to Indonesia's economy, but many MSMEs unable to manage their business well. PT Selula Dwiphaloka Technologi is an MSME, a family business located in Bekasi City, Indonesia, that sells a custom-design machine for B2B customer. The data were collected using business coaching methods, a qualitative research that used to mapping MSME’s condition and problem, then take a corrective action to implement solutions for improvement. The result shows that the MSME don’t have a written SOP that can be used as guidance so the personal selling activity can be done consistenly, and also the website and company profile of MSME don’t look very interesting. So, the solution is by developing SOP of personal selling, improving the website and company profile to support marketing activities. Surveys were also conducted to support evidence of the improvement result. As the results, there was a significant increase in the respondents' assessment of the visual aspects, information and overall appearance of the new website and company profile compared to the old ones. This study aims to help PT Selula Dwiphaloka Teknologi manage their marketing activities by creating SOP of personal selling, designing new website and company profile proposal